Acute compartment syndrome: Reducing the risk - Pearse, M; Nanchahal, J (2008)
Acute limb compartment syndrome is a surgical emergency characterized by raised pressure within an unyielding tissue compartment. Although there is commonly a history of trauma there are a number of causes of compartment syndrome, which includes iatrogenic insults. The key clinical feature of a compartment syndrome in the conscious patient is severe pain out of proportion to the injury and aggravated by passive muscle stretch. Intracompartmental pressure measurements remain the only objective method of diagnosing an acute compartment syndrome. Although it is subject to false positives, interpreting the pressures in relation to the systemic blood pressure helps confirm the diagnosis when the clinical findings are equivocal and provides essential information in unconscious or uncooperative patients. Successful treatment of an acute compartment syndrome involves prompt, early diagnosis followed by an adequate surgical decompression of all four compartments of the leg by fasciotomies. Delay in diagnosis is almost invariably associated with a poor outcome and loss of limb function. As acute compartment syndromes typically occur in young patients with an average work-life expectancy of up to 30 years, a poor outcome results in severe loss of productivity.